Viscoelastic Study of Hemostasis Disorders Associated with Echis ocellatus Envenoming in North Benin Using a Quantra Analyzer - Sébastien Larréché; Roland Benes Chacha; Noé Sodjinou; Seidou Alassane Ouorou; Eric Ganhouingnon; Edith Aloukoutou Layo; Bruno Mégarbane; Achille Massougbodji; Jean-Philippe Chippaux (Toxins)
Echis ocellatus envenomings are a public health problem in West Africa, leading to bleeding and hypocoagulability. The aim of this study was to assess the hemostasis disorders associated with E. ocellatus envenoming. Envenomed patients with an abnormal whole blood clotting test (WBCT) were prospectively included at Tanguiéta, Benin. A WBCT with a sequential reading (i.e., at 20, 30, and 60 min), viscoelastic analysis (VA) using the Quantra analyzer, and blood count were performed on admission. VA and the WBCT were also assessed at 4, 8, 12, 24, 48, and 72 h after antivenom administration. Nineteen patients were included. On admission, the main results were an absence of a clot on VA and a slight decrease in platelets. Clot time gradually decreased over time while clot stiffness, fibrinogen, and platelet contributions to stiffness increased. Sequential reading improved the sensitivity of the WBCT. At H48, all patients with recurrence bleeding after antivenom administration had an abnormal WBCT while patients with a normal WBCT never had bleeding during their follow-up. VA allows the identification of various hemostasis disorders. Hypofibrinogenemia was the main disorder that persisted for several days after treatment. A WBCT with a sequential reading is an effective alternative for monitoring hypocoagulability in the absence of a laboratory.